Forecasting of Significant Wave Height and Period at Western Waters of Ternate Island, North Maluku - Mohammad Ridwan Lessy; Rommy Mudafar Abdullah (TECHNO: JURNAL PENELITIAN, 2021)
The water of West Ternate Island is open waters which are very dynamic oceanographic conditions. One of them is ocean waves that are strongly related to wind friction. This study aims to analyze the height and wave period that occurred in the western part waters of Ternate Island based on wind data for 10 years. It is expected that the results of this study will be useful for policymakers in the sustainable management of coastal areas in Ternate City. This research used Wilson Method to estimate the wave height in four seasons.  The data collected includes the maximum wind direction and speed during the period 2009-2018 obtained from the Meteorological and Geophysical Station of Baabullah Airport, Ternate City. Wind data will be transformed to stability correction and wind stress factor to determine height and period of wave. The results showed that in The West Season and Transition Season 1 (TS 1), the wind direction is more dominant moving from the Northwest to the Southeast with an average maximum speed of 17.71 knots. During the observation year, significant wave height (Hs) formed in the Western Season period as high as 1.25 m – 2.75 m while in Transition Season 1 the wave height was between 1.0 m – 2.31m. While in the Eastern Season period the wave height that occurs ranges from 0.61 m – 1.55 m and in the MP2 period ranges from 0.67 m – 1.43 m. In the Western Season, the wave period ranges from 4.67 – 6.82 seconds, and in Transition Season 1 between 4.45 – 6.44 seconds. While in the eastern season the wave period ranges from 3.29 – 4.89 seconds and in Transition Season 2 (TS 2) ranges from 3.43 – 4.68 seconds.